Rethinking Film Festivals in the Pandemic Era and After - de Valck, Marijke; Damiens, Antoine (Framing Film Festivals, 2023)
This is an open access book. This edited collection aims to document the effects of Covid-19 on film festivals and to theorize film festivals in the age of social distancing. To some extent, this crisis begs us to consider what happens when festivals can't happen; while films have found new (temporary) channels of distribution (most often in the forms of digital releases), the festival format appears particularly vulnerable in pandemic times. Imperfect measures, such as the move to a digital format, cannot recapture the communal experience at the very core of festivals. Given the global nature of the pandemic and the diversity of the festival phenomenon, this book features a wide range of case studies and analytical frameworks. With contributors including established scholars and frontline festival workers, the book is conceived as both a theoretical endeavour and a practical exploration of festival organizing in pandemic times. Marijke de Valck is Associate Professor of film and media studies at Utrecht University, Netherlands, where she co-directs the master program in film and television cultures. Her research deals with film festivals, transnational media cultures, media industries, and art cinema. Her publications include Film Festivals: From European Geopolitics to Global Cinephilia (2007), the co-edited Film Festival: History, Theory, Method, Praxis (2016) and Art and Activism in the Age of Systemic Crisis: Aesthetic Resilience (2020). She is co-founder of the Film Festival Research Network, co-editor of Palgrave's Framing Film Festivals series and co-editor of the festivals review section in NECSUS. Antoine Damiens is a Research Associate at York University, Toronto, where they recently completed a MITACs Accelerate Postdoctoral Fellowship. His research examines the politics and history of film festivals, queer film/video, and minoritized archives. Their first book, LGBTQ Film Festivals: Curating Queerness, was published in 2020. Antoine Damiens co-edits, with Marijke de Valck, the Film Festival Reviews section in NECSUS. .